Development of Inflammatory Bowel Disease in Children With Juvenile Idiopathic Arthritis Treated With Biologics. Issue 2 (18th November 2022) - Broekaert, Ilse J.; Klein, Ariane; Windschall, Daniel; Rogalski, Betina; Weller-Heinemann, Frank; Oommen, Prasad; Küster, Michael; Foeldvari, Ivan; Minden, Kirsten; Hospach, Anton; Hufnagel, Markus; Berger, Thomas; et al.
Abstract : Objective: The aim of our study was to describe the distinct features of inflammatory bowel disease (IBD) in juvenile idiopathic arthritis (JIA) patients and to identify risk factors for its development. Methods: Data from the German biologics in pediatric rheumatology registry (Biologika in der Kinderrheumatologie) collected between 2001 and 2021 were analyzed retrospectively. Results: In 5009 JIA patients, 28 developed confirmed IBD before the age of 18 years: 23 (82.1%) with Crohn disease (CD), 4 (14.3%) with ulcerative colitis (UC), and 1 (3.6%) with IBD-unclassified (IBD-U). The incident rate of IBD during 20 years of observation was 0.56% (0.46% for CD, 0.08% for UC, and 0.02% for IBD-U), of whom 20.3% were HLA-B27 positive, 25% had enthesitis-related arthritis, and 14.3% psoriatic arthritis. Within 90 days before IBD diagnosis, 82.1% (n = 23) received treatment with etanercept (ETA), 39.3% (n = 11) non-steroidal anti-inflammatory drugs, 17.9% (n = 5) systemic corticosteroids, 8 (28.6%) methotrexate (MTX), 14.3% (n = 4) sulfasalazine, 10.7% (n = 3) leflunomide, and 3.6% (n = 1) adalimumab and infliximab, respectively. The incidence of IBD was lower in patients treated with MTX, but higher in patients treated with ETA except if ETA was combined with MTX. Also in patients on leflunomide or sulfasalazine, the IBD incidence was higher. Conclusions: In our JIA cohort, an increased IBD incidence is observed compared to the general population, and the ratio of CD to UC is markedly higher hinting at a distinct phenotype of IBD. Pretreatment with MTX seems to be protective. Treatment with ETA does not prevent IBD development and JIA patients treated with leflunomide and sulfasalazine may be at an increased risk for IBD development. Abstract :